APPLICATION OF FUNDAMENTAL TECHNOLOGIES OF NEURO-LINGUISTIC PROGRAMMING (NLP) IN THE COMMUNICATION MODEL OF SOCIAL EDUCATORS (EDUCATION IN THE 21ST CENTURY, 2024)
Utilization of artificial intelligence in various fields is a challenge to be competitive in the professional domain. The imperative of the time is to enhance the professional knowledge, constantly improve the functions of specialists and train them, taking into account the interdisciplinary applications of various sciences, as well as the mastery and application of cutting-edge technologies. From this standpoint, the social pedagogue has its role, through the utilization of various technologies in the communication model in the course of consultations with the child, with the intention of enhancing the effectiveness of the activities. When we consider the further development of a social pedagogue in the context of integral sciences, it is necessary to master the technological components of related sciences, which will enable them to carry out their professional duties in a novel quality and format. The professional spheres of the activities of social pedagogues are multifaceted so the functions implemented by them are diverse. From this standpoint, the richer the methodological knowledge of the research specialist is, the greater the chances of success are, and the smaller the risks will be.The functions of the social pedagogue will gain new levels of development in the professional arena, if they try to apply the knowledge of neuro-linguistic programming, as well as the components of fundamental technologies during their activities. Currently, neuro-linguistic programming is no longer a monopoly for the activities carried out by psychologists, psychiatrists, HRM specialists, doctors, and businesspeople. Through the application of various diagnostic, prognostic, preventive and art-therapeutic technologies, the social pedagogue partially involves components of fundamental neuro-linguistic technologies in their practice enabling them to carry out such activities more efficiently.
Keywords: neuro-linguistic programming; functions of the social pedagogue; improvement cycle; non-verbal communication; fundamental technological components